2017
DOI: 10.21815/jde.017.051
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Online Approach to Teaching Evidence‐Based Dentistry with Web 2.0 Technology

Abstract: At many dental schools, evidence-based dentistry (EBD) is taught in a traditional lecture format. To avoid the constraints of lectures, in 2012 the EBD unit was redesigned for online delivery at the Arthur A. Dugoni School of Dentistry at the University of the Pacific with a Web 2.0 tool called Voicethread. The aim of this study was to assess the impact of Voicethread-based online learning on students' perceptions of learning EBD, their participation and engagement, and their acceptance of this new online deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…Our results show a positive attitude related to TEL application in periodontics education, which was also emphasized by other studies in dental education. 2,[42][43][44] This finding might suggest that TEL implementation in undergraduate dental courses motivate students through their learning process. The application of a questionnaire to assess students' attitudes was highlighted by Shoaib et al as an essential tool in evaluating impacts on educational outcomes, especially in a leaner-center approach.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our results show a positive attitude related to TEL application in periodontics education, which was also emphasized by other studies in dental education. 2,[42][43][44] This finding might suggest that TEL implementation in undergraduate dental courses motivate students through their learning process. The application of a questionnaire to assess students' attitudes was highlighted by Shoaib et al as an essential tool in evaluating impacts on educational outcomes, especially in a leaner-center approach.…”
Section: Discussionmentioning
confidence: 84%
“…New technologies have led to the implementation of innovative learning and teaching methods in dental education away from traditional educational pedagogies. [1][2][3] Among different types of technologies, technology-enhanced learning (TEL) is the application of information and communication technologies in the delivery of education. 4,5 In this systematic review, the concept of TEL was adopted to describe any learning methods that implement computers, mobile devices, software, virtual reality, virtual learning environment and videos as educational tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active learning approaches such as problem-based learning, case studies and practical training have been shown to be more successful than the traditional model, providing a dynamic and engaging experience for dental students. [15][16][17][18] Practical training would ideally use human teeth to mimic clinical work. 19 However, human-extracted teeth with real cases of secondary caries progression are difficult to obtain, and thus, other alternatives must be used in the teaching process.…”
Section: Introductionmentioning
confidence: 99%
“…Practical training in detection and management of secondary caries could be an alternative tool for improving dentist and undergraduate student competencies. Active learning approaches such as problem‐based learning, case studies and practical training have been shown to be more successful than the traditional model, providing a dynamic and engaging experience for dental students …”
Section: Introductionmentioning
confidence: 99%